THE LANDSCAPE PROJECT, THE FUNCTIONS AND THE USE OF THE URBAN PARKS - THE PARK 13 OF MAY. - Ana Rita Sá Carneiro Ribeiro (Clio: Revista de Pesquisa Histórica, 1998)
The content of the text approaches the historical process of the creation of Parque 13 de Maio, the first urban park of the city of Recife, focusing on the different expressions of elaborated landscape design, European influences in the treatment of the landscape and the economic, administrative and cultural aspects that have subjugated the physical planning of the city and the consolidation of free spaces and greens of public character. Also emphasized are aspects of the visual composition of the park and its relation with the environment, function and use, including problems faced in that space, to show, among other contributions, that the changes occurred in the projects implemented relate to the social needs of users over time.